The THE LEGEND OF ANGLING DHARMA AS INSPIRATION IN WORK OF COMIC ART - Munazil, Jamil; Muharrar, Syakir; Mujiyono, Mujiyono (Arty: Jurnal Seni Rupa, 2022)
The study project that was written, took the theme "The Legend of Angling Dharma As Inspiration in Creating Comic Art". The purposes of this study project are 1) Visualize the author's ideas and creations regarding the legend of Angling Dharma in the form of a comic book so that it can be enjoyed by various groups. 2) Presenting information and education to others about the legend of Angling Dharma. The materials used in making the Angling Dharma comic book work are paper, ink, and watercolors. The tools used in the work are brushes, palettes, pencils, sharpeners, rubber erasers, rulers, drawing pens, scanners, and computers. The work technique that the author uses is a combination of manual and digital techniques or hybrid techniques. The creation of the work uses an approach that seems realistic so that it can be enjoyed by all people by going through several stages of work, namely preliminary, pre-production, production, and post-production. The production process of the "Angling Dharma" comic uses several stages, namely storyboarding, sketching, inking, coloring, adding word balloons, editing and finishing. This Study Project produces a comic book entitled “Angling Dharma” which is divided into 26 chapters and is packaged in 54 pages, with dimensions of A4 (21cm x 29.7cm). The comic "Angling Dharma" can be accessed online, through the website and social media prepared by the author.